1999
DOI: 10.1620/tjem.189.267
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Toxicity of Gallium Arsenide in Alveolar Macrophages Evaluated by Magnetometry, Cytochemistry and Morpholegy.

Abstract: Gallium arsenide (GaAs), a chemical compound of gallium and arsenic, causes various toxic effects including pulmonary diseases in animals. Since the toxicity is not completely investigated, GaAs has been used in workplaces as the material of various semiconductor products. The present study was conducted to clarify the toxicity of GaAs particles in the alveolar macrophages of hamsters using magnetometry, enzyme release assays and morphological examinations. Alveolar macrophages obtained from hamsters by trache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…LDH release was increased in GaAsexposed cells. According to DNA electrophoresis and the TUNEL method, apoptotic changes failed to be detected [3]. Because AsCl 3 alone caused effects identical to those of GaAs on magnetometry and LDH release in macrophages, and Ga 2 O 3 did not show significant effects, it was concluded that As was responsible for the toxicity to macrophages [22].…”
Section: Arsenic and Compounds Used In The Microelectronics Industrymentioning
confidence: 99%
See 4 more Smart Citations
“…LDH release was increased in GaAsexposed cells. According to DNA electrophoresis and the TUNEL method, apoptotic changes failed to be detected [3]. Because AsCl 3 alone caused effects identical to those of GaAs on magnetometry and LDH release in macrophages, and Ga 2 O 3 did not show significant effects, it was concluded that As was responsible for the toxicity to macrophages [22].…”
Section: Arsenic and Compounds Used In The Microelectronics Industrymentioning
confidence: 99%
“…Iron oxide particles with a mean geometric diameter of 0.26 lm were used as the magnetometric index. Male hamsters [2,3] or F344/NS1c rats [20] were anesthetized and bronchoalveolar lavage fluid was obtained. The harvested cells, about six million cells, were divided into two groups: one group was exposed to different doses of chemicals, and the other group was exposed to phosphate-buffered saline as a control.…”
Section: Toxicity Evaluation Using Cell Magnetometry and Other Suppormentioning
confidence: 99%
See 3 more Smart Citations